Modeling and Optimization of Technological Processes of Railway Transport - Tursunov Zakir Shuxratovich; Ergashev Bahromjon Olimjon o‘g‘li (International Journal on Orange Technologies, 2022)
In this article the nature of the disorder depends on the human factor and human factors technical and technological break the success of technical and technological means prescribed by which came out was to analyze a statistical correlation between the presence of. An assessment of the state of labor protection in railway transport is given, the causes and sources of occupational injuries are given. For the prevention of dangerous and harmful labor factors at the workplaces of railway transport enterprises, it is proposed to create and implement the Concept of Labor Safety and prevention of industrial and occupational risk ofpersonnel. The proposed concept contributes to reducing the risk of occupational injuries and occupational diseases, creating more comfortable working conditions for personnel.